Experiential education against environmental denial in environmental ethics education: a case study - Grušovnik, Tomaž; Arzenšek, Ana (Journal of Education Culture and Society, 2020)
Recent research shows that ‘environmental denial’ (the denial of anthropogenic impact on the natural world) plays an important role in environmental education. The difficulty in changing our detrimental habits stems from the fact that identities in our societies are bound up with consumerist practices. Because we cannot simply give up practices that shape our identity, environmental education has to fi nd ways of substituting unhealthy habits with environmentally acceptable ones. One method of achieving this is through experiential education based on experiences with the natural world and their importance for identity formation. The paper presents a case study involving experiential education in environmental ethics, implemented at the university level. Findings show that the implementation of experiential education technique (fi eld trip) yielded positive results in connection with students’ overcoming of environmental denial and consequential change of their environmental outlook.